Direct-to-Implant Versus 2-Stage Breast Reconstruction: Which Technique Is Better? An Analysis of 104 Patients at a Single Institution. Issue 2 (11th August 2022) - Piper, Merisa L.; Rios-Diaz, Arturo J.; Kimia, Rotem; Cunning, Jessica; Broach, Robyn; Wu, Liza; Serletti, Joseph; Fosnot, Joshua
Abstract : Background: Two-stage (TS) implant-based reconstruction is the most commonly performed method of reconstruction after mastectomy. A growing number of surgeons are offering patients direct-to-implant (DTI) reconstruction, which has the potential to minimize the number of surgeries needed and time to complete reconstruction, as well as improve health care utilization. However, there are conflicting data regarding the outcomes and complications of DTI, and studies comparing the 2 methods exclusively are lacking. Methods: Patients undergoing implant-based reconstruction after mastectomy within a large interstate health system between 2015 and 2019 were retrospectively identified and grouped by reconstruction technique (TS and DTI). The primary outcomes were a composite of complications (surgical site occurrences), health care utilization (reoperations, unplanned emergency department visits, and readmissions), and time to reconstruction completion. Risk-adjusted logistic and generalized linear models were used to compare outcomes between TS and DTI. Results: Of 104 patients, 42 underwent DTI (40.4%) and 62 underwent TS (59.6%) reconstruction. Most demographic characteristics, and oncologic and surgical details were comparable between groups ( P > 0.05). However, patients undergoing TS reconstruction were more likely to be publicly insured, have a smoking history, and undergo skin-sparing instead of nipple-sparing mastectomy. The composite outcome of complications, reoperations, and health care utilization was higher for DTI reconstruction within univariate (81.0% vs 59.7%, P = 0.03) and risk-adjusted analyses (odds ratio, 3.78 [95% confidence interval [CI], 1.09–13.9]; P < 0.04). Individual outcome assessment showed increased mastectomy flap necrosis (16.7% vs 1.6%, P < 0.01) and reoperations due to a complication (33.3% vs 16.1%; P = 0.04) in the DTI cohort. Although DTI patients completed their aesthetic revisions sooner than TS patients (median, 256 days vs 479 [ P < 0.01]; predicted mean difference for TS [reference DTI], 298 days [95% CI, 71–525 days]; P < 0.01), the time to complete reconstruction (first to last surgery) did not differ between groups (median days, DTI vs TS, 173 vs 146 [ P = 0.25]; predicted mean difference [reference, DTI], −98 days [95% CI, −222 to 25.14 days]; P = 0.11). Conclusions: In this cohort of patients, DTI reconstruction was associated with higher complications, reoperations, and health care utilization with no difference in time to complete reconstruction compared with TS reconstruction. Further studies are warranted to investigate patient-reported outcomes and cost analysis between TS and DTI reconstruction.